Developing Critical Thinking Skills among Young Learners through Innovative Learning Models - Dian Hikmayana (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This study investigates the effectiveness of innovative learning models in developing critical thinking skills among young learners in elementary schools located in Ponorogo, Indonesia. In the context of 21st-century education, fostering critical thinking from an early age is essential to prepare students for complex and dynamic life challenges. Employing a qualitative case study approach, this research explores how models such as Project-Based Learning (PjBL), inquiry-based instruction, and collaborative learning contribute to enhancing students’ cognitive engagement, reasoning ability, and problem-solving skills. Data were collected through classroom observations, semi-structured interviews with teachers, and documentation of student projects across four elementary schools. The findings reveal that innovative pedagogical approaches significantly increased student participation, encouraged reflective inquiry, and supported the development of independent thought. Teachers reported that learners became more confident in expressing their ideas, analyzing real-life problems, and working collaboratively with peers. Despite the positive outcomes, the study also identified challenges such as limited instructional time, lack of teacher training, and insufficient learning resources, particularly in rural settings. The research concludes that integrating innovative learning models into primary education can serve as a strategic pathway to foster critical thinking, provided that adequate support systems and teacher development programs are in place. These findings offer valuable insights for educators, school leaders, and policymakers seeking to improve educational quality and student competencies in Ponorogo and similar contexts.